Control of Non-Communicable Diseases in the Indonesian Regulations of Health - Ni Putu Rastiti; Ni Ketut Supasti Dharmawan; Ika Widi Astuti; I Gde Sastra Winata (Babali Nursing Research)
Introduction: Non-communicable diseases are chronic diseases that are the most common causes of death worldwide, including in Indonesia. The increase in the prevalence of NCDs occurs year after year and becomes a problem for national health and budget. This challenge is why the enactment of Law Number 17 of 2023 on Health was subsequently followed by the implementation of Government Regulation Number 28 of 2024 on the Implementation Regulations of Law Number 17 of 2023 on Health. This research aims to understand the prevention of non-communicable diseases outlined in this regulation.